Strategic trading behavior and price distortion in a manipulated market: anatomy of a squeeze - MERRICKJR, J; NAIK, N; YADAV, P (Journal of Financial Economics, 2005)
This paper investigates an attempted delivery squeeze in a bond futures contract traded in London. Using cash and futures trades of dealers and customers, we analyze their strategic trading behavior, price distortion, and learning in a market manipulation setting. We argue that marked differences in settlement failure penalties in the cash and futures markets create conditions that favor squeezes. We recommend that regulators require special flagging of forward term repurchase agreements on the key deliverables that span futures contract maturity dates, and that exchanges mark-to-market their contract specifications more frequently, or consider a cash-settled contract on a basket of bonds.